Reactive and Active Power Output Optimization in a Wind Farm Using the Particle Swarm Optimization Technique - Cherkaoui, Nazha; Belfqih, Abdelaziz; Mariami, Faissal El; Sabri, Omar; Boukherouaa, Jamal; Dazahra, Mohamed Nouh; Majdoub, Meriem (International Journal of Advanced Engineering Research and Science, 2020)
In the recent years, the contribution of the wind power to energy supply has increased considerably; hence, the wind farms have to be able to participate to the grid power stability. In this paper, an optimization algorithm allows obtaining the reactive and active power dispatch in a wind power plant is presented. The aim of the proposed algorithm is to minimize the power losses and the difference between the reactive power obtained and required by the transmission system operator at the point of common coupling. The simulation results show the validity and the performance of the proposed algorithm.